2015
DOI: 10.1007/s10854-015-2730-z
|View full text |Cite
|
Sign up to set email alerts
|

Wettability optimization analysis of lead-free solders with Taguchi method

Abstract: In this paper, the wettability of lead-free solders on substrates with fluxes was studied based on reflow process and Taguchi method. Effects of different control factors, including solder materials, fluxes, substrate materials and atmosphere on the wettability of the lead-free solder joints were examined and calculated. Moreover, the effect of rare earth Eu on the wetting of SnAgCu solder was investigated, the effect mechanism was analyzed too. The wettability optimal design in the lead-free solders system ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because of the large number of factors present in the sanding process related to the wood, sandpaper, and machines, it is necessary to apply an experimental planning method to minimize the number of experimental conditions that need to be investigated. The Taguchi method provides such an approach (Zhang et al 2015). According to Hamzaçebi (2016) the Taguchi method is an effective and robust experimental design technique that determines the most important factors and their impact on the optimization of process parameters through the reduction of number of experiments performed.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the large number of factors present in the sanding process related to the wood, sandpaper, and machines, it is necessary to apply an experimental planning method to minimize the number of experimental conditions that need to be investigated. The Taguchi method provides such an approach (Zhang et al 2015). According to Hamzaçebi (2016) the Taguchi method is an effective and robust experimental design technique that determines the most important factors and their impact on the optimization of process parameters through the reduction of number of experiments performed.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] One of the reasons is the difficulty in obtaining pure brookite since it is a thermo-dynamically metastable form with a relatively lower symmetry and higher surface energy, which cause the brookite formation to be usually accompanied by a secondary phase such as anatase and/or rutile. 13,14,[20][21][22] In 1966, Keesmann 23 was the first to prepare pure brookite through the hydrothermal treatment of amorphous TiO 2 obtained by hydrolysis of titanium tetraisopropoxide in the presence of NaOH solution, in which Na + ions were considered to stabilize the brookite lattice. Similarly, Mitsuhashi and Watanabe 24 found that brookite can be obtained through the hydrothermal treatment of a fresh coprecipitate prepared from TiCl 4 and CaCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%